Child-adult differences in muscle activation - A review - Dotan, R.; Mitchell, C.; Cohen, R.; Klentrou, P.; Gabriel, D.; Falk, B. (Pediatric Exercise Science, 2012)
Children differ from adults in many muscular performance attributes such as size-normalized strength and power, endurance, fatigability and the recovery from exhaustive exercise, to name just a few. Metabolic attributes, such as glycolytic capacity, substrate utilization, and VO2 kinetics also differ markedly between children and adults. Various factors, such as dimensionality, intramuscular synchronization, agonist-antagonist coactivation, level of volitional activation, or muscle composition, can explain some, but not all of the observed differences. It is hypothesized that, compared with adults, children are substantially less capable of recruiting or fully employing their higher-threshold, type-II motor units. The review presents and evaluates the wealth of information and possible alternative factors in explaining the observations. Although conclusive evidence is still lacking, only this hypothesis of differential motor-unit activation in children and adults, appears capable of accounting for all observed child—adult differences, whether on its own or in conjunction with other factors.